Excel macros for dummies - Alexander, Michael, 1972- (--For dummies., 2015)
Ready-made Excel macros that will streamline your workflow Excel Macros For Dummies helps you save time, automate, and be more productive, even with no programming experience at all. Each chapter offers practical macros that you can implement right away, with practical exercises that extend your knowledge and help you understand the mechanics at work. You'll find the most effective Excel macros for solving common problems, and explanations of why and where to use each one, plus invaluable guidance and step-by-step instruction for applying them effectively. Learn how to customize your applica.